Establishing Customer Satisfaction to Increase Customer Loyalty in Collin Beach Hotel - Walter Tabelessy; Rainier H. Sitaniapessy; Dian M. Lekatompessy (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is conducted on the basis of phenomena related to experiential marketing, service quality, customer satisfaction and customer loyalty. This research is conducted through a quantitative survey at the Collin Beach Hotel in the village of Latuhalat, Ambon, as the object of research. The number of samples used in this research is 124 respondents, which is a Non-Probability Sampling collected using the Purposive Sampling technique. For hypothesis testing, this research applies PLS-SEM with SmartPLS application. The results of the research show that experiential marketing has a positive and significant influence towards customer satisfaction. Service quality has a positive and significant influence towards customer satisfaction. Customer satisfaction has a positive and significant influence towards customer loyalty